Visual Analysis Of Body Signals In Smoker Data To Understand Health Impacts On Python - Nasrulloh, Anas; Yusuf, Muhamad; Mas’ud, Ibnu; Toifur, Tubagus; Ikhwanudin, Aolia; Syamhalim, Agianto (Journal Sensi: Strategic of Education in Information System, 2025)
In this study, researchers found that 44.4% of people had blood pressure less than 120/80, 58.2% had fasting blood sugar <= 99, 47.7% had hemoglobin > 17.2, and 62% had oral problems and teeth caused by smoking. This research was carried out by visualizing the impact of smoking on blood pressure, fasting blood sugar, hemoglobin and the mouth and teeth in the body using body signal of smoking data obtained from Kaggle which was analyzed and presented in the form of a pie chart using Python.